KONSEP PENDIDIKAN KARAKTER SISWA DALAM KAJIAN KITAB ADABUL ‘ALIM WAL MUTA’ALLIM - Atho'illah (Fakultas Agama Islam Universitas Yudharta Pasuruan, 2021)
Education and teaching are not the same thing, because education does not only focus on the transfer of knowledge, but there are aspects of value transformation and character formation in it. The general basis of noble character is usually obtained from obedience to legal provisions, socio-cultural norms and religious norms. Education is a process that occurs in humans which is carried out, both programmed and takes place by itself which has the intention of developing self-potential as the nature of humans themselves, including body and soul. Character is a collection of values ​​that lead to a system that underlies the thoughts, attitudes and behaviors that are displayed. Guidance and nurturing parents and teachers are very important for physical growth and development of cognition, emotion, personality, and social awareness. The basic need for character education is to make people who have noble personality and behavior to become useful figures for those around them.